1995
DOI: 10.1364/ol.20.002048
|View full text |Cite
|
Sign up to set email alerts
|

Ball lens reflections by direct solution of Maxwell’s equations

Abstract: Thisisa preprintof apaperintended forpublicationina journalorproceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As mentioned before, the cusp catastrophe can be caused by such an aberrated focus. Relatively large ball-lenses have been intensively studied for optical-fiber communication systems [6][7][8]. Its characteristics are well studied by geometric optics under paraxial approximation [5].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the cusp catastrophe can be caused by such an aberrated focus. Relatively large ball-lenses have been intensively studied for optical-fiber communication systems [6][7][8]. Its characteristics are well studied by geometric optics under paraxial approximation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing ball lens mode converter performance through a more reliable design has been discussed by many researchers using theoretical or experimental methods. Correctly predicting the refractions from a ball lens into an SMF [1] and accurately calculating the coupling efficiency from an LD into an optical fiber through a ball lens using the exact solution to Maxwell's equations for the beam scattering from a sphere have been accomplished [2]. Maxwell's equations compared to a conventional method using geometrical and diffraction analysis have also revealed that the optimum coupling efficiency depends on sufficiently fine discretization of the distances between the source and fiber from the ball lens [3].…”
Section: Introductionmentioning
confidence: 99%